Mechanisms of high-level resistance to quinolones in urinary tract isolates of Pseudomonas aeruginosa. - Yoshida, T (1994)
Twenty-eight strains of Pseudomonas aeruginosa with various degrees of norfloxacin resistance were isolated from patients with urinary tract infections. P. aeruginosa strains (norfloxacin MICs, 3.13 to 200 micrograms/ml) were transformed by either pPAW207 or pNF111 plasmid DNA, which included either the gyrA or nfxB gene, respectively. For transformants with pPAW207, norfloxacin MICs decreased 8- to 128-fold. It was suggested that moderate and high degrees of resistance to norfloxacin were expressed as a result of alterations in gyrA. No strain manifesting only an alteration in nfxB permeability was observed. The MICs of norfloxacin (200 micrograms/ml) for two P. aeruginosa strains, GN17605 and GN17434-2, were decreased following transformation not only by pPAW207 but also by pNF111. Analysis of outer membrane proteins disclosed the presence of a 54,000-Da protein in these parent strains that was not expressed in the pNF111 transformants. The level of accumulation of norfloxacin by the pNF111 transformant of GN17605 was higher than that by the parent strain. The norfloxacin susceptibility of DNA gyrase subunit A purified from GN17605 was only 1/35th that of the gyrase containing a subunit A from P. aeruginosa PAO1. These findings suggest that GN17605 is a gyrA-nfxB double mutant and that strain GN17434-2 possesses double mutations in both nfxB and some unknown gene.